Screening for High-Risk Human Papillomavirus Reveals HPV52 and HPV58 among Pediatric and Adult Patient Saliva Samples - Hunter Hinton; Lorena Herrera; Sofia Valenzuela; Katherine M. Howard; Karl Kingsley (MDPI AG, 2024)
Previous research has demonstrated that the human papillomavirus (HPV) can infect a wide range of human tissues, including those within the oral cavity. High-risk oral HPV strains have been associated with the development and progression of oral cancers, including oral squamous cell carcinomas. Although many studies have examined the prevalence of the high-risk strains HPV16 and HPV18, far fewer have assessed the prevalence of other high-risk HPV strains. An approved study protocol was used to identify HPV52 and HPV58 among clinical samples (n = 87) from a saliva biorepository. Quantitative polymerase chain reaction (qPCR) and validated primers for HPV52 and HPV58 were used to facilitate this screening. This screening demonstrated that a total of n = 4/45 or 8.9% of adult saliva samples harbored high-risk HPV52, and n = 2/45 or 4.4% tested positive for high-risk HPV58. In addition, a total of n = 6/42 or 14.3% of the pediatric saliva samples tested positive for high-risk HPV, including n = 5/42 or 11.9% with HPV52 and n = 3/42 or 7.1% for HPV58. These data demonstrate the presence of the high-risk oncogenic HPV52 and HPV58 strains among both adult and pediatric clinical patient samples. More detailed longitudinal research must be conducted to determine whether this prevalence may be increasing or decreasing over time. In addition, these data strongly support public health prevention efforts, such as knowledge and awareness of the nine-valent HPV vaccine covering additional high-risk strains, including HPV52 and HPV58.